Pharmacokinetics of adjusted-dose 8-hourly lopinavir/ritonavir in HIV-infected children co-treated with rifampicin - Rabie, Helena (J Antimicrob Chemother, 2019)
OBJECTIVES: To evaluate the proportion of children with lopinavir C(min) ≥1 mg/L when receiving a novel 8-hourly lopinavir/ritonavir dosing strategy during rifampicin co-treatment. METHODS: HIV-infected children on lopinavir/ritonavir and rifampicin were enrolled in a prospective pharmacokinetic study. Children were switched from standard-of-care lopinavir/ritonavir-4:1 with additional ritonavir (1:1 ratio) twice daily to 8-hourly lopinavir/ritonavir-4:1 using weight-banded dosing. Rifampicin was dosed at 10–20 mg/kg/day. After 2 weeks, plasma samples were collected ∼2, 4, 6, 8 and 10 h after the morning lopinavir/ritonavir-4:1 dose, ALT was obtained to assess safety and treatment was switched back to standard of care. ClinicalTrials.gov registration number: NCT01637558. RESULTS: We recruited 11 children in two weight bands: 5 (45%) were 10–13.9 kg and received 20–24 mg/kg/dose of lopinavir and 6 (55%) children weighed 6–9.9 kg and received 20–23 mg/kg/dose of lopinavir. The median age was 15 months (IQR = 12.6–28.8 months). The median (IQR) lopinavir C(min) was 3.0 (0.1–5.5) mg/L. Seven (63.6%) of the 11 children had C(min) values ≥1 mg/L. Children with a lopinavir mg/kg dose below the median 21.5 were more likely to have C(min) <1 mg/L (P = 0.02). There was a strong positive correlation between lopinavir and ritonavir concentrations. No associations were found between lopinavir AUC(2–10) and age, sex, weight, nutritional status or mg/kg/dose of lopinavir. CONCLUSIONS: These data do not support the use of 8-hourly lopinavir/ritonavir at studied doses. Evaluation of higher doses is needed to optimize treatment outcomes of TB and HIV in young children.